Nivolumab Induced Thyroid Dysfunction: Unusual Clinical Presentation and Challenging Diagnosis - Iadarola, Carmine; Croce, Laura; Quaquarini, Erica; Teragni, Cristina; Pinto, Sara; Bernardo, Antonio; Fonte, Rodolfo; Marinò, Michele; Rotondi, Mario; Chiovato, Luca (Frontiers in Endocrinology, 2019)
In recent years, immune checkpoint inhibitors (ICIs) had a great impact in cancer therapy. ICIs display a peculiar toxicity profile, which is characterized by autoimmune-like manifestations against multiple organs, including endocrine glands. We hereby report the case history of two patients who experienced nivolumab-induced endocrine immuno-related Adverse Events (irAEs). Thyroid dysfunction in both patients presented with a low serum level of TSH. However, endocrine evaluation showed a completely different etiology and clinical evolution. The two patients’ histories indicate that nivolumab can cause a large spectrum of thyroid and endocrine dysfunctions resulting in cumbersome diagnostic problems. In these peculiar patients the evaluation of endocrine experts is warranted.